Biomarkers of exposure to SVOCs in children and their demographic associations: The TESIE Study. (October 2018) - Hoffman, Kate; Hammel, Stephanie C.; Phillips, Allison L.; Lorenzo, Amelia M.; Chen, Albert; Calafat, Antonia M.; Ye, Xiaoyun; Webster, Thomas F.; Stapleton, Heather M.
Abstract: Semi-volatile organic compounds (SVOCs) are used extensively in consumer and personal care products; electronics; furniture; and building materials and are detected in most indoor environments. As a result, human exposure to mixtures of SVOCs is wide-spread. However, very few studies have measured biomarkers of exposure to multiple SVOC classes, and exposure determinants have not been thoroughly explored, particularly for young children. In this study, we investigated biomarkers of exposure to SVOCs among children (age 3–6 years), who may experience higher exposures and be more susceptible to adverse health outcomes than other age groups. We enrolled 203 participants in the Toddlers Exposure to SVOCs in Indoor Environments (TESIE) study (181 provided urine samples and 90 provided serum samples).We quantified 44 biomarkers of exposure to phthalates, organophosphate esters (OPEs), parabens, phenols, antibacterial agents and per- and polyfluoroalkyl substances (PFASs); we detected 29 of the 44 biomarkers in >95% of samples, and many biomarkers were detected at higher median concentrations than those previously reported in the U.S. general population. Demographic characteristics were associated with differences in concentrations. In general, non-Hispanic white race and higher maternal education were associated with lower concentrations, even after adjusting for other potential confounding variables. Our results suggest that outdoor temperature at the time of biospecimen collection may be a particularly important and under-evaluated predictor of biomarker concentrations; statistically significant relationships were observed between 10 biomarkers and outdoor temperature at the time of collection. A complex correlation structure was also observed among the biomarkers assessed. By and large, statistically significant correlations between biomarkers of exposure to phthalates, parabens, phenols, and OPEs were positive. Conversely, although PFASs were positively correlated with one another, they tended to be negatively correlated with other biomarkers where significant associations were observed. Taken together, our results provide evidence that the assessments of SVOC-associated health impacts should focus on chemical mixtures. Highlights: Biomarkers of SVOC exposure were assessed in North Carolina children age 3–6 years. We detected 29 of the 44 biomarkers of SVOC exposure in >95% of children's samples. Demographic characteristics were associated with many SVOC biomarkers. Outdoor temperature was positively correlated with the levels of 10 biomarkers. Biomarkers of SVOC exposures were commonly positively correlated with each other.